2014
DOI: 10.1016/j.yfrne.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Avian circadian organization: A chorus of clocks

Abstract: In birds, biological clock function pervades all aspects of biology, controlling daily changes in sleep: wake, visual function, song, migratory patterns and orientation, as well as seasonal patterns of reproduction, song and migration. The molecular bases for circadian clocks are highly conserved, and it is likely the avian molecular mechanisms are similar to those expressed in mammals, including humans. The central pacemakers in the avian pineal gland, retinae and SCN dynamically interact to maintain stable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
111
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 158 publications
(263 reference statements)
1
111
1
15
Order By: Relevance
“…In birds, non visual light stimuli are mainly received in the retina, the hypothalamus (via the retinal hypothalamic tract, RHT), and in the pineal gland (Gwinner and Brandstätter 2001 ). At present, it is still unclear how this information is integrated between the different components of the avian central circadian system (Cassone 2013 ), but it is evident that the pineal gland plays a much bigger role than it does in mammals. One model, the "neuroendocrine loop", suggested that the retina, pineal gland, and an SCN like structure in the hypothalamus all contain "damped" oscillators that are capable of self producing oscillation only if photic or endocrine stimuli are present (Cassone and Menaker 1984 ).…”
Section: Light and Circadian Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In birds, non visual light stimuli are mainly received in the retina, the hypothalamus (via the retinal hypothalamic tract, RHT), and in the pineal gland (Gwinner and Brandstätter 2001 ). At present, it is still unclear how this information is integrated between the different components of the avian central circadian system (Cassone 2013 ), but it is evident that the pineal gland plays a much bigger role than it does in mammals. One model, the "neuroendocrine loop", suggested that the retina, pineal gland, and an SCN like structure in the hypothalamus all contain "damped" oscillators that are capable of self producing oscillation only if photic or endocrine stimuli are present (Cassone and Menaker 1984 ).…”
Section: Light and Circadian Rhythmsmentioning
confidence: 99%
“…Instead, the "internal resonance" model proposed that the pineal gland and the SCN sustain and stabilize each other through the expression of independent circadian outputs, such as the cyclic expression of specific clock genes in the SCN and the release of melatonin from the pineal gland (Gwinner 1989 ). Communication between the SCN and peripheral clocks in birds is accomplished via a combination of humoral signals and direct neural connections, which are far less understood in birds than in mammals (Cassone 2013 ). Humoral signals directly affect hypothalamic function, while neural outputs project to the central nervous systems and peripheral sites, impacting a broad range of peripheral physiological functions, including that of the pineal gland.…”
Section: Light and Circadian Rhythmsmentioning
confidence: 99%
“…Ptaki posiadają więc trzy oscylatory w CCS, które in vitro działają niezależnie od siebie, generując własny rytm uwalniania różnych związków chemicznych. W warunkach in vivo wypadkowa działań wszystkich oscylatorów skutkuje wspólnym rytmem biologicznym wielu procesów życiowych organizmu (14,21,33,56,66,90). Mechanizm współdziałania trzech oscylatorów CCS ptaków na poziomie molekularnym nie jest jeszcze, niestety, poznany.…”
Section: Artykuł Przeglądowy Reviewunclassified
“…Zmiany konformacji białka Cry są modyfikowane nie tylko przez światło, ale i pole magnetyczne. Cry jest także prawdopodobnie odpowiedzialny za utrzymywanie okresów bezsenności w trakcie nocnych przelotów ptaków migrujących, gdyż wykazywano wtedy szczegól-nie wysoką ekspresję jego genów (14,37,39,62,63).…”
Section: Artykuł Przeglądowy Reviewunclassified
See 1 more Smart Citation